2016
DOI: 10.1002/app.44540
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of polypropylene/poly(lactic acid) bicomponent meltblown

Abstract: The bicomponent meltblown process offers to associate two polymers in the same fiber generating fibrous media with new properties. In this study, we associate polypropylene (PP) and poly(lactic acid) (PLA), from renewable sources, polymers. The influence of primary air flow rate and the structural properties of the PP/PLA bicomponent meltblown are compared to PP and PLA monocomponent meltblown. The structural properties include fiber morphology and diameter, packing density, permeability, thermal shrinkage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…One of the most commonly used polymers in the melt-blown technique is polypropylene (PP) [ 8 , 9 ] endowed with great rheological and physical properties. However, PP is produced from non-renewable resources and is more widely used in bone tissue engineering and suture than as a skin substitute [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly used polymers in the melt-blown technique is polypropylene (PP) [ 8 , 9 ] endowed with great rheological and physical properties. However, PP is produced from non-renewable resources and is more widely used in bone tissue engineering and suture than as a skin substitute [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned melting behavior revealed that only the POM domain performed crystallization in the POM/PLLA blends, and the PLLA domain is partially miscible with the POM one in the amorphous phase. This might enhance the interfacial adhesion of the POM and PLLA phases and therefore made the as-spun bicomponent fibers undergo an ultimate tensile stress like as-spun pure POM fiber under the post-drawing process [47]. In addition, the optical microscopic observation is also indicative of the fact that the incorporation of PLLA seems not to influence the diameter distribution and structure of filaments.…”
Section: Resultsmentioning
confidence: 99%
“…where the Φ is the porosity of the paper sheet (%), V is the volume of the paper (cm 3 ), Vf is the volume of fiber (cm 3 ), ρ is the apparent density of the paper (g/cm 3 ), and ρf is the density of the fibers (g/cm 3 ), which were 1.550 g/cm 3 for cellulose (Lindsay and Brady 1993), and 1.240 g/cm 3 for polylactic acid fiber (Rungiah et al 2017). The difference between the porosity of polylactic acid papers and wood fiber papers might be because polylactic acid fibers are much stiffer than wood fibers, cannot be fibrilated by the beating process, and the lack of hydroxyl groups, which prevents the polylactic acid fibers from entangling and establishing bonding between each other.…”
Section: Role Of Wood Fiber Amount In Tuning the Physical Properties Of Composite Papermentioning
confidence: 99%